The Mean Difference of Hemostatic Factors in Severe Preeclampsia and Eclampsia - Setia, Dyhan Purna; Ferry, Ferdinal; Djanas, Dovy (Andalas Obstetrics And Gynecology Journal, 2020)
The aim of this study was to see the difference in the mean ratio of sodium levels between pregnancy with severe preeclampsia and eclampsia. The method in this research is an analytical study using a cross sectional design. The research was conducted in the delivery room Dr. M. Djamil Padang from 15 January 2016 to 31 December 2017. There were 60 patients as research subjects, the sample was divided into 2 groups, namely severe preeclampsia (PEB) and eclampsia. Anamnesis and physical examination were then carried out to obtain data and clinical diagnosis. The data were recorded in a research form that had been provided, then the blood electrolytes were examined for sodium and potassium. Statistical analysis to assess meaning using the T-test. The results showed that in the PEB and Eclampsia groups, it was found that multiparity parity had the highest respondents. This is in accordance with the literature where the incidence of preeclampsia is more often found at gestational age near term. The conclusion of this study there was no significant difference in the mean sodium ratio between preeclampsia, PEB and eclampsia. Keywords: pregnancy condition, PEB, eclampsia, platelet, PT, APTT, and D-Dimer